Factors that Influence Usage of Financial Services in South Africa - Loyiso Maciko (AL-ARBAH: Journal of Islamic Finance and Banking, 2026)
Purpose - The differential factors that influence access to and usage of financial services in rural and urban South Africa were examined in this study, highlighting the distinct challenges faced by each population. Method  - Drawing on data from FinScope surveys conducted across nine South African provinces from 2012 to 2017, binomial logistic regression was used to investigate how various factors affect financial inclusion. Result - The findings indicate marked differences between rural and urban areas. Rural residents are more likely to encounter barriers associated with geographic isolation, larger household sizes, lower levels of educational attainment and greater distance from financial institutions. By contrast, urban residents benefit from closer proximity to services, yet disparities in the usage of financial services persist, particularly in relation to gender, employment status and perceptions of banking costs. Implication - The results underscore that financial inclusion strategies cannot be applied uniformly across rural and urban areas. Targeted interventions are required to address the specific barriers faced by each group. Originality - The originality of this study lies in its integrated framework, which simultaneously analyses traditional factors and emerging factor. This comprehensive approach moves beyond fragmented analyses found in prior research by offering a holistic understanding of financial service usage in South Africa. Keywords: Financial inclusion, Financial literacy, Access, Usage